EKSPERIMEN UJI KEKUATAN TARIK KOMPOSIT DENGAN RESIN EPOXY DAN PENGUAT SERAT KULIT SINGKONG MENGGUNAKAN METODE HAND LAY UP - Irvan Randi Siregar; Muhammad Fa’iz Alfatih; Sabri Alimi (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The development of science and technology is currently growing in all fields, including the field of vehicle construction, building construction, industry, and also the field of material engineering, especially composites. Composite is a material system which is a mixture of two or more combinations and has many advantages including lighter weight, adjustable strength and higher resistance and corrosion resistance. In this tensile test to determine the effect of length on tensile strength, strain and modulus of elasticity in each sample. This study experimented with how to test the tensile strength of composites with epoxy resin and cassava peel fibers using the hand lay up method. has a fiber volume of 25%, 50% and 75% with the greatest value is the tensile strength of 4,942 Mpa with a fiber volume of 25% then the tensile elastic modulus of this composite material shows the largest at 50% volume, which is 941.5 Mpa.